A Review of Child and Adolescent Diagnostic Interviews for Clinical Practitioners. (December 2015) - Leffler, Jarrod M.; Riebel, Jordanna; Hughes, Honore M.
The publication of the DSM-5 poses a challenge for many interview instruments due to the changes for many of the diagnoses. Six of the more widely used and studied interview instruments (structured and semistructured) were reviewed with a focus on usefulness for the practicing clinician and researcher. Use of these types of assessment procedures can facilitate the accuracy of diagnoses given by potentially reducing clinician bias. Each interview instrument varied in its strengths and characteristics related to amount of flexibility associated with administration of items; breadth of coverage of diagnoses based on DSM-IV ; time required for administration; presence of screening items or modular format; and psychometric support for its reliability and validity, as well as amount of training required for use, and costs associated with acquiring and learning the format. Recommendations were made regarding the utilization of different instruments for specific diagnostic questions along with future recommendations for enhancing the format and utility of these instruments, especially in relation to the publication of the DSM-5 .